2015
DOI: 10.1111/cei.12679
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD11c and EMR2 on neutrophils: potential diagnostic biomarkers for sepsis and systemic inflammation

Abstract: SummaryThere is a need for cellular biomarkers to differentiate patients with sepsis from those with the non-infectious systemic inflammatory response syndrome (SIRS). In this double-blind study we determined whether the expression of known (CD11a/b/c, CD62L) and putative adhesion molecules [CD64, CD97 and epidermal growth factor (EGF)-like molecule containing mucin-like hormone receptor (EMR2)] on blood neutrophils could serve as useful biomarkers of infection and of non-infectious SIRS in critically ill pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
4
36
0
Order By: Relevance
“…Neither of these is normally associated with neutrophil activation. EMR2 is induced already in G-CSF-treated BCs, which fits with the upregulation seen in sepsis (37). The PG receptors PTGER2 and OXER1, the chemotaxis receptor FPR2, the ATP receptor P2RY13, GPR97 normally involved in B-lymphocyte migration, and the chemokine receptor CCR1 are all mainly downregulated in G-CSF-treated compared with untreated cells, indicating less responsiveness to chemotaxins, to proinflammatory mediators, and to danger signals (ATP).…”
Section: Gpcr-related Genessupporting
confidence: 68%
“…Neither of these is normally associated with neutrophil activation. EMR2 is induced already in G-CSF-treated BCs, which fits with the upregulation seen in sepsis (37). The PG receptors PTGER2 and OXER1, the chemotaxis receptor FPR2, the ATP receptor P2RY13, GPR97 normally involved in B-lymphocyte migration, and the chemokine receptor CCR1 are all mainly downregulated in G-CSF-treated compared with untreated cells, indicating less responsiveness to chemotaxins, to proinflammatory mediators, and to danger signals (ATP).…”
Section: Gpcr-related Genessupporting
confidence: 68%
“…Finally, 86 studies were included after two updated searches in February 2015 and September 2016 (Fig. 1) (Abidi et al 2008; Ahmadinejad et al 2009; Al-Nawas et al 1996; Anand et al 2015; Balc et al 2003; Barati et al 2010; Battista et al 2016; Bell et al 2003; Beqja-Lika et al 2013; Carpio et al 2015; Castelli et al 2004; Clec’h et al 2006; de Pablo et al 2013; Dorizzi et al 2006; Du et al 2003; Endo et al 2012; Farag et al 2013; Feng et al 2012; Gaini et al 2006; Garnacho-Montero et al 2014; Gerrits et al 2013; Giamarellos-Bourboulis et al 2008; Gibot et al 2004; Godnic et al 2015; Guven et al 2002; Han et al 2016; Harbarth et al 2001; Hoenigl et al 2013; Hou et al 2012, 2016; Hsu et al 2011; Ishikura et al 2014; Ivancevic et al 2008; Jekarl et al 2013, 2014; Jiang et al 2015; Kim and Zhang 2012; Kofoed et al 2007; Latour-Perez et al 2010; Lewis et al 2015; Li et al 2013a; Lin et al 2015; Matera et al 2013; Mat-Nor et al 2016; Mearelli et al 2014; Meynaar et al 2011; Miglietta et al 2015; Miller et al 1999; Muthiah et al 2007, Naeini and Montazerolghaem 2006; Oshita et al 2010; Papadimitriou-Olivgeris et al 2015; Ratzinger et al 2013; Reichsoellner et al 2014; Righi et al 2014; Rivera-Chavez and Minei 2009; Rogina et al 2014; Romualdo et al 2014; Ruiz-Alvarez et al 2009; Sakr et al 2008; Scherpereel et al 2006; Schulte et al 2011; Selberg et al 2000; Seok et al 2012; Shozushima et al 2011; Sierra et al 2004; Su et al 2012, 2013; Sungurtekin et al …”
Section: Resultsmentioning
confidence: 99%
“…However, Lewis SM et al . recently demonstrated that EMR2 is a potential biomarker for SIRS and it is associated with the extent of organ failure26. Child C or decompensated end-stage liver disease often leads to multiple organ failure427.…”
Section: Discussionmentioning
confidence: 99%
“…The ligation of EMR2 could increase neutrophil adhesion, migration and anti-microbial mediator production and could enhance the systemic inflammation11. Furthermore, other studies had shown that EMR2 expression on the neutrophil increased in patients with SIRS and correlated with the extent of organ failure12. Its gene variant could sensitize mast cells to IgE-independent vibration-induced degranulation13.…”
mentioning
confidence: 99%